The Spiritual Illusion: Redux - Herman, Jonathan R. (Method & theory in the study of religion, 2015)
In this response to Knut Melvær’s discussion of “The Spiritual Illusion: Constructive Steps Toward Rectification and Redescription,” I clarify some of the theoretical and methodological background that informed the original article, redress places where Melvær appears to have misread or miscast my positions, and offer some suggestions as to what may really be most at stake in this “spiritual” dispute.